Use of mobile applications in citizen security - Juan Chumbe Chocce; Laberiano Andrade-Arenas; Domingo Hernández Celis; Michael Cabanillas-Carbonell (Bulletin of Electrical Engineering and Informatics, 2023)
An abstract is often presented separately from the article, so it must be able to in the following article the use of the mobile application is recommended as a tool that serves public safety because currently crimes of extortion and fraud are committed by making false calls to people's mobile devices. Therefore, the objective of this research is to help families with their welfare and safety and motivate the use of mobile applications. In the present work the situation, task, action, dan result (STAR) methodology was applied to elaborate the present work, this technique will allow improving the difficulties of the people. This methodology is very important because it is used to evaluate the circumstances in which people find themselves, a sequence must be followed to achieve the proposed objectives. The result obtained is an average of 84.5% on the design of the mobile prototype; being approved by the experts. The beneficiaries of the research are citizens through the mobile application.